Real-world experience with capmatinib in MET exon 14-mutated non-small cell lung cancer (RECAP): a retrospective analysis from an early access program. (June 2022) - Illini, Oliver; Fabikan, Hannah; Swalduz, Aurélie; Vikström, Anders; Krenbek, Dagmar; Schumacher, Michael; Dudnik, Elizabeth; Studnicka, Michael; Öhman, Ronny; Wurm, Robert; Wannesson, Luciano; Peled, Nir; et al.
Background: Patients with non-small cell lung cancer (NSCLC) presenting with mesenchymal–epithelial transition ( MET ) exon 14 skipping mutation have an unfavorable prognosis with standard treatments. Capmatinib is a selective MET inhibitor, which showed promising efficacy in this patient population in early trials. Methods: We performed a retrospective, international, multicenter efficacy and safety analysis in patients with NSCLC treated with capmatinib in an early access program between March 2019 and December 2021. Results: Data from 81 patients with advanced MET exon 14 mutated NSCLC treated with capmatinib in first- or later-line therapy were analyzed. Median age was 77 years (range, 48–91), 56% were women, 86% had stage IV disease, and 27% had brain metastases. For all patients, the objective response rate (ORR) to capmatinib was 58% (95% CI, 47–69), whereas it was 68% (95% CI, 50–82) in treatment-naïve and 50% (95% CI, 35–65) in pretreated patients. The median progression-free survival was 9.5 months (95% CI, 4.7–14.3), whereas it was 10.6 months (95% CI, 5.5–15.7) in first-line and 9.1 months (95% CI, 3.1–15.1) in pretreated patients. After a median follow-up of 11.0 months, the median overall survival was 18.2 months (95% CI, 13.2–23.1). In patients with measurable brain metastases ( n  = 11), the intracranial ORR was 46% (95% CI, 17–77). Capmatinib showed a manageable safety profile. Grade ⩾ 3 treatment-related adverse events included peripheral edema (13%), elevated creatinine (4%), and elevated liver enzymes (3%). Conclusion: In patients with MET exon 14 skipping mutation, capmatinib showed durable systemic and intracranial efficacy and a manageable safety profile. This analysis confirms previously reported phase II data in a real-world setting.